PENGARUH SOFT SKILL DAN MOTIVASI KERJA TERHADAP KESIAPAN KERJA (Studi Pada Mahasiswa Prodi Manajemen Bisnis Syariah STAIN Mandailing Natal) - Niwana Pulungan; Sari Fitri, Rizka Ar Rahmah (CV. Adiba Aisha Amira, 2025)
This research aims to determine the influence of soft skills and work motivation on work readiness of STAIN Mandailing Natal Sharia Business Management Study Program Students. This research uses a quantitative approach and the population in this study are active students of the Sharia Business Management study program, STAIN Mandailing Natal, class of 2020, where the sample was 41 respondents with a sampling technique using Saturated Sampling with Likert scale measurements. The results of this research show that Soft Skill influence the work readiness STAIN Mandailing Natal Sharia Business Management Study Program Students with a tvalue of 2,911 > ttable 1,686 and a significance value of 0,006 < 0,05 and work motivation also influence the work readiness of STAIN Mandailing Natal Sharia Business Management Study Program Students with a tvalue of 4,691 > ttable 1,686 and a significance value of 0,000 < 0,05, and there is an influence of soft skills and work motivation on work readiness of STAIN Mandailing Natal Sharia Business Management Study Program Students with a Fvalue of 27,210 > Ftable 3,24 and a Significance value of 0,000< 0,05. The coefficient of determination (R2) is 0,589, which means soft skill and work motivation simultaneously influence work readiness by 58.9%.